Quality Of Nursing Care In The Kingdom: A Systematic Review Of Nursing Team Management In Saudi Healthcare - Rasha Hamidi Marzouq Al-Mutairi, Sarah Nasser Alrabayyi, Manal Alewi Ali ALRashidi, Reem Ibrahim Al-Harabi, Malak Salem Zaben Alotaibi, Manahi Mohammed Abid Almutairi, Manal Youssef Al-Mowis; Ibtesam Sanad Awad Alrasheedi, Mashael Mohammed AlAgeeli, Sarah Talaq Fatim Almutairi, Mona Mohd Hussain Alamir, Abdullah Maashi Fayadh Alenezi, Shamah Salem Alrashidy (Journal of International Crisis and Risk Communication Research, 2024)
Background: The quality of nursing care is a critical aspect of healthcare, directly impacting patient outcomes and safety. In Saudi Arabia, nursing team management plays a significant role in determining the effectiveness of care delivery. However, various challenges, such as leadership styles, team collaboration, and work environment conditions, affect the overall quality of nursing care in the Kingdom. This systematic review aims to explore how nursing team management influences care quality within Saudi healthcare settings, in alignment with Vision 2030 reforms. Aim: This study aims to evaluate the role of nursing team management, including leadership practices, team collaboration, and organizational governance, in enhancing the quality of nursing care in Saudi Arabia. Method: A systematic search was conducted across PubMed, Scopus, CINAHL, and Google Scholar for studies published between 2020 and 2024. A total of 150 articles were identified, and after screening and full-text review, 10 studies were selected for inclusion. The data extraction process focused on leadership styles, teamwork, work environment, professional development, and governance related to nursing care quality. Results: The findings reveal that transformational leadership, effective team collaboration, a supportive work environment, and continuous professional development significantly contribute to improved patient outcomes and nursing care quality. Studies indicate that organizational support and involvement in decision-making also play a crucial role in enhancing nurse performance and job satisfaction. Conclusion: Nursing team management is essential to the quality of care in Saudi Arabia. Effective leadership, collaboration, and professional governance are key drivers of high-quality nursing care. These findings inform future strategies for improving nursing practices in Saudi healthcare settings in line with the Kingdom’s Vision 2030.